Analysis of Constitutional Court Decision Number 01/PHPU-PRES/XVII/2019 Related to Presidential Election Disputes - Farizal Pranata Bahri; Megawati Barthos (Journal Research of Social Science, Economics, and Management, 2023)
The study desires to find out the basic considerations and analysis of the Constitutional Court regarding the dispute over the results of the 2019 Presidential General Election. The type of research used is normative research. The results obtained from this study are that Bawaslu has too broad authority and even the Constitutional Court cannot re-examine the results of the Bawaslu decision because it is final. It is contrary to the principle of checks and balances applied in Indonesia. Therefore, the Drafters view that Law Number 7 of 2017 concerning General Elections needs to be replaced by a regulation that can expand the authority of the Constitutional Court or at least the Constitutional Court has the authority to re-examine decisions from election management bodies.